Scientific Writing Training for Teachers in Kindergarten for Children in Jambi City - Ariyani, Rika; Darni, Darni; Darsiah, Darsiah (Jurnal Masyarakat Mengabdi, 2024)
Training on writing scientific papers for Kindergarten teachers in Buah Hati Jambi City aims to improve the professionalism and skills in writing scientific papers of teachers. This training was carried out face to face for one day involving 10 teachers. The methods used include lectures, question-and-answer sessions, group discussions, and practical exercises. The evaluation showed very enthusiastic and active participation from the participants, with significant improvements in the ability to write scientific papers. Evaluation results through writing assignments, satisfaction surveys, observations, and in-depth interviews show that participants can understand and apply techniques for writing scientific papers better. This training has a positive short-term impact in the form of increasing technical skills and teacher confidence and is expected to have a long-term impact on improving the quality of education through the implementation of evidence-based teaching practices. Overall, this training made a significant contribution in improving the professional competence of the Buah Hati Kindergarten teachers in Jambi City. Recommendations for future training include increasing length, individual coaching sessions, and the use of interactive learning media. This training is an important first step in efforts to improve the quality of education in the region.